Time preferences and health behaviour: A review - Lydia Lawless; Andreas C. Drichoutis; Rodolfo M. Nayga (Agricultural and Food Economics, 2013)
In this paper, we review published studies to assess the influence of time preferences on human health behaviour. Our review indicates that elicited discount rates for health have been found to be higher than those for money in both the social and private context. We discuss the importance of discount rates for public policy since high time discount rates can contribute to governmental emphasis on acute health care, rather than preventive health care. We then examine how time preferences interrelate with specific health concerns such as smoking or obesity. We find that even when time preferences are elicited in the monetary domain, they can be successful in predicting smoking cessation and likewise for obesity. We also discuss how time preferences relate with teen risk taking behavior.
Keywords: 330; Time preference; Health domain; Risk aversion; Discount rate; Health behaviour